The Role of Stem Cells in the Etiology and Pathophysiology of Endometriosis - Hufnagel, Demetra; Li, Fei; Cosar, Emine; Krikun, Graciela; Taylor, Hugh S. (Seminars in Reproductive Medicine, 2015)
Human endometrium is a dynamic organ that normally undergoes repetitive cyclic regeneration. To enable this rapid regeneration, it is not surprising that the endometrium contains a reservoir of progenitor stem cells. However, this pool of cells that allows the growth of the endometrium also allows for unrestrained growth that can reach beyond the endometrium. In this review, we will address the role of stem cells in endometriosis. Recent characterization of stem cell populations within human endometrium has opened the possibility of understanding their physiologic as well as their pathologic roles. While stem cells are critical to the cyclic regeneration of a healthy endometrium, we have shown that both endometrium-derived and bone marrow-derived stem cells can migrate to ectopic sites and contribute to the development of endometriosis. Furthermore, endometriosis interferes with the normal stem cell trafficking to the uterus that is necessary for endometrial growth and repair. Altered stem cell mobility and engraftment characterize this disease.
Keywords: endometrium; endometriosis; stem cells; inflammation